A Prospective Multi-Center Audit of Nutrition Support Parameters Following Burn Injury. Issue 4 (July 2015) - Kurmis, Rochelle; Heath, Kathryn; Ooi, Selena; Munn, Zachary; Forbes, Sharon; Young, Vicki; Rigby, Paul; Wood, Kate; Phillips, Frances; Greenwood, John
<x xml:space="preserve">Abstract</x> The importance of nutrition support delivery to the severe burn-injured patient is well recognized, however, nutrition provision to the patient may be sub optimal in practice. The aim of this study was to conduct a prospective multi-center audit across Australia and New Zealand using the Joanna Briggs Institute Burns Node Nutrition audit criteria. Thirty-four patients with severe burn injury (≥20% TBSA in adults and ≥10% TBSA in children) were identified on admission or on referral to the Dietitian at the eight participating Burn Units between February 1, 2012 and April 30, 2012 for inclusion in the study. De-identified patient data was analyzed using the Joanna Briggs Institute, Practical Application of Clinical Evidence System. Compliance with individual audit criterion ranged from 33 to 100%. Provision of prescribed enteral feed volumes and weekly weighing of patients were highlighted as key areas for clinical improvement. Clinical audit is a valuable tool for evaluating current practice against best evidence to ensure that quality patient care is delivered. The use of the Joanna Briggs Institute Burns Node audit criteria has allowed for a standardized multi-center audit to be conducted. Improving nutrition support delivery in burn patients was identified as a key area requiring ongoing clinical improvement across Australia and New Zealand. Clinician feedback on use of the audit criteria will allow for future refinement of individual criterion, and presentation of results of this audit has resulted in a review of the Bi-National Burns Registry nutrition quality indicators.